The efficacy of low-dose anlotinib as a first-line treatment for frail patients with lung adenocarcinoma and its bridging significance for subsequent treatment: case report - Huang, Jiawei; Wang, Bei; Wu, Bomeng (Frontiers in Medicine, 2025)
This case report describes a 49-year-old male patient with advanced lung adenocarcinoma (cT3N3M1b, stage IVA), brain metastases, an ECOG PS of 3, negative driver gene status and low PD-L1 expression (TPS 1%). Traditional treatment options were limited. Following a multidisciplinary team consultation, the patient was prescribed a low dose of anlotinib (8 mg/day on d1–14, q21d) as a first-line treatment. Following two cycles of treatment, there was a significant improvement in symptoms (muscle strength recovery and the ability to walk independently), and an imaging assessment revealed shrinkage of the primary tumour and brain metastases. After seven cycles, the ECOG PS improved to 0, but after 11 cycles, progression occurred (tumour enlargement and new effusion). Switching to a combination of pemetrexed disodium and bevacizumab resulted in another response. The patient’s overall survival reached 16 months (anlotinib PFS: 9 months). This case suggests that low-dose anlotinib may serve as a bridging therapy for patients with advanced non-small cell lung cancer (NSCLC) and a poor general condition, improving their physical status and creating conditions for subsequent treatment. The potential of anlotinib for first-line application and strategies for overcoming drug resistance warrant further exploration.